AB0417 Biological drugs in the treatment of rheumatoid arthritis: real life data in a brazilian multicentric study. (12th June 2018) - Gomides, A.; Pinheiro, G.; Santos, A.; Albuquerque, C.; Giorgi, R.; Radominski, S.; Pereira, I.; Guimarães, M.; Bértolo, M.; Júnior, P.L.; Bonfiglioli, K.; Brenol, C.; et al.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic disease, characterised by inflammatory involvement of the synovial joints. The "treat to target" concept is well established in the rheumatologic community, however, in many patients, especially in developing countries, its implementation is not feasible. Considering the high costs of treatment com of RA and the limited national epidemiological data available on this disease, we sought to describe the profile of use of biological drugs in Brazilian patients with RA to help the decision-making process by public health managers. Objectives: To describe the frequency and time of use of biological drugs in Brazilian patients with rheumatoid arthritis. Methods: The REAL – RA in real life in Brazil – is a multicenter prospective cohort study, with twelve-month follow-up period. To be included in this study, consecutive patients from 11 tertiary rheumatology centres had to meet the 1987 ACR or the 2010 ACR/European League Against Rheumatism (EULAR) criteria. Data were collected during routine clinical care and previous medical records were used as secondary sources. The present study present data taken from the participants' initial assessment. This research was approved by the Ethics Committees of each centre. Results: A total of 1125 patients were analysed. 89% were women with a mean age of 56.6 years. The main clinic data were: DAS 28 (median)=3.52, HAQ (median)=0.87 and CDAI (median)=9. 1022 (90.84%) used synthetic DMARDs and 406 (36.09%) biologic therapy. The frequency of use of the biologic therapy was: abatacept (73 patients/6.49%), etanercept (66/5.87%), tocilizumab (60/5.33%), adalimumab (54/4.8%), infliximab (50/4.44%), rituximab (49/4.36%), golimumab (37/3.29%), certolizumab (17, 1.51%). The time of use of the biological drugs is presented in table 1. Conclusions: The therapeutic profile of this cohort of Brazilian RA patients shows some interesting results. The relatively high number of patients on biologics, compared to other studies, may be related to fact that the centres involved were reference centres, probably dealing with more difficult cases. References: [1] Azevedo AB, Ferraz MB, Ciconelli RM. Indirect Costs of Rheumatoid Arthritis in Brazil. Value in Health2008;11(5):869–877. [2] Boonen A, Severens JL. The burden of illness of rheumatoid arthritis. Clin Rheumatol2011;30(Suppl 1):S3–S8. Disclosure of Interest: None declared